2007
DOI: 10.3406/paleo.2007.5223
|View full text |Cite
|
Sign up to set email alerts
|

Chalcolithic Agricultural Life at Grar, Northern Negev, Israel: Dry Farmed Cereals and Dung-Fueled Hearths

Abstract: Résumé: Il est généralement admis qu’au Chalcolithique (4700-3800 avant J.-C.) dans le Nord-Néguev, les champs sont situés dans des plaines inondables et que s’y pratique une irrigation par eaux de ruissellement. Nous présentons ici une étude menée à Grar, site chalcolithique se trouvant sur le plateau de loess des rives du Nahal Grar, pour laquelle ont été examinés quantitativement des assemblages phytolithiques de deux aires de fouille distinctes. Les sédiments sont composés d’importantes quantités de phytol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Our results support previous suggestions that during the Chalcolithic period agricultural practice in the Southern Levant included both high water availability conditions (Rosen and Weiner, 1994), which was accomplished not by building diversion walls and dams, but by placing the fields in floodplain areas (Hillel, 1994), and close to riverbank topographical features other than floodplains (Katz et al, 2007) that are less flat or level, but offer a greater amount of flow accumulation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results support previous suggestions that during the Chalcolithic period agricultural practice in the Southern Levant included both high water availability conditions (Rosen and Weiner, 1994), which was accomplished not by building diversion walls and dams, but by placing the fields in floodplain areas (Hillel, 1994), and close to riverbank topographical features other than floodplains (Katz et al, 2007) that are less flat or level, but offer a greater amount of flow accumulation.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, by providing another perspective for evaluating the issues of water management and wadi resource exploitation of the Northern Negev Chalcolithic sites, our results support previous suggestions of dry farming (Katz et al, 2007), and flood-irrigation agricultural practice (Rosen and Weiner, 1994). We therefore conclude that the exploitation of the resources of wadi environments, such as soils, water and vegetation, was enhanced by the use of natural runoff sink areas rather than by the construction of irrigation systems such as dams or diversion walls along the wadis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…30% (Katz et al, 2007;Shahack-Gross et al, 2003). Here we showed that comparable precision can be achieved in a very short time, even when some of the most challenging samples are counted, namely those that contain other archaeologically irrelevant biogenic opaline fossils, and many unidentifiable fragments of opal.…”
Section: Discussionmentioning
confidence: 69%
“…The agricultural remains are less conspicuous in the loesscovered rolling plains of the northern Negev, but more evidence is appearing (Katz and Gilead, 2007;Levy andAlon, 1983, 1987;Winter-Livneh et al, 2010). West of Beer Sheva, at the site of Shiqmim (Fig.…”
Section: Northern Negev E Nahal Beer Sheva Floodplain: Shiqmimmentioning
confidence: 94%